Infestation Pattern of Macrosiphum rosae and Tetranychus sp. in Rose Plants (Rosa hybrida) Cultivated in Protected and Open Cultivation in Kathmandu District - Thapa, Vinod Kumar; Budha, Prem Bahadur (Journal of Natural History Museum, 2009)
A study was carried out from January to December 2005 in four different sites of Kathmandu district. Infestation pattern of mite and aphid was observed in different canopy levels (top, middle and bottom) of rose plant. Top part of the plant showed highest aphid infestation followed by middle part and bottom part showed little or no infestation. Similar trend was observed in case of mite, with highest distribution in top, middle part and relatively low in bottom part. Macrosiphum rosae and Tetranychus sp. were found to be the dominant pests infesting rose plants in open and protected conditions respectively. Key words: Rose; mites; aphids; infestation; canopy level; Kathmandu Journal of Natural History Museum Vol. 23, 2008 Page 88-91